Water exchange in Van Phong bay, Khanh Hoa province by hydrodynamic model - Tran Van, Chung; Nguyen Huu, Huan; Thai Ngoc, Chien (Vietnam Journal of Marine Science and Technology, 2021)
The analysis of the average wind field from 1979 to 2018 showed that in the Van Phong bay area, the hydrodynamic process is mainly influenced by tidal currents when the frequency of weak wind accounts for a high proportion and the wind regime is controlled entirely by locality and less likely to alter tidal currents significantly. Based on the shallow water hydrodynamic finite element model (FEM), a two-dimensional hydrodynamic model has been developed for Van Phong bay to study hydrodynamic features, especially exchange capacity of seawater with the open sea. The results show that the daily average daily exchange of water in Van Phong bay is about 1,845.46 × 106 m3/day, equivalent to 34.7% water volume in the bay. In the rainy season, the typical daily average water exchange in Van Phong bay is about 2,136.04 × 106 m3/day, equivalent to 43.19% of the volume of water in the bay. In the dry season, the typical daily average total water exchange in Van Phong bay is about 1,825.56 × 106 m3/day, corresponding to 34.35% of water volume in the bay.